Being Flawless: Beauty Representation in L’Oréal Paris Skincare Advertisements - Ni Luh Putu Andika Wahyuni; Putu Nur Ayomi (Innovations in Language Education and Literature, 2024)
Advertising serves as a key medium for promoting products, often conveyed through posters, images, or videos. The language and visuals in advertisements significantly shape consumers’ perceptions of the product's effectiveness. This study examines the verbal and non-verbal signs in L'Oréal Paris skincare video advertisements, using a qualitative approach supported by Saussure's semiotic theory and Barthes' framework on connotation and denotation. Data were analyzed through observation and interpretation to uncover how advertisements convey meaning. The findings reveal that the representation of beauty in L'Oréal Paris advertisements transcends skin tone, emphasizing the ideal of flawless skin. Models of diverse skin tones are consistently presented, showcasing a universal aspiration for radiant, blemish-free, and well-maintained skin. The study highlights how both verbal elements, such as slogans and product descriptions, and non-verbal cues, including colors, visuals, and models, contribute to crafting a compelling message. This research provides insights into how semiotics enhances the communication of beauty ideals, offering implications for advertising strategies aimed at inclusivity and universal appeal.